High-throughput, motility-based sorter for microswimmers such as C. elegans1. Issue 13 (7th July 2015) - Yuan, Jinzhou; Zhou, Jessie; Raizen, David M.; Bau, Haim H.
<x xml:space="preserve">Abstract</x> This paper describes the design, fabrication, characterization, and applications of a high-throughput motility-based sorter for microswimmers such as C. elegans.